Environmental perception of students of fundamental education in the rural area of the City of Paulista, Paraíba, Brazil (Research, Society and Development, 2021)
Through a school inserted in the field, the understanding of the students' environmental perception in relation to the environment is elementary. The objective of this work was to identify the perception about the environment of students in the final years of elementary school in the city of Paulista-PB. The research had as object of study students from two rural schools in the city of Paulista-PB, from March to June 2021, with the participation of 136 students. The research was descriptive and qualitative and obtained data through a form relating to the theme of the environment. In view of the analysis of this study, it was recorded that 89% of students from both schools are aware of the definition of the term about the environment, but, find it difficult to perceive themselves as an integral part of the environment. A lack of students in perceiving environmental issues in an interdisciplinary way was identified, however, a positive participation of the school in the process of actions and projects with the environmental theme was evidenced, contributing to the critical development of students in the face of environmental problems.